2019
DOI: 10.1002/jsfa.10024
|View full text |Cite
|
Sign up to set email alerts
|

Propolis: types, composition, biological activities, and veterinary product patent prospecting

Abstract: Propolis is a resinous substance composed of a mixture of different plant parts and molecules secreted by bees. Chemically, it is defined as a complex matrix containing biologically active molecules with antibacterial, antifungal, antiviral, antiparasitic, hepatoprotective, and immunomodulatory activities. It is widely employed in cosmetic formulations and pharmaceutical products and is one of the most widely used natural products. However, the effects and strength of these biological activities depend on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 115 publications
(120 reference statements)
0
70
0
2
Order By: Relevance
“…Propolis (or bee glue) is a complex mixture of molecules obtained from several resinous secretions (e.g., resins, mucilage, gums, lattices, leaf buds) collected by worker-bees from different plant species [ 8 ]. Its composition is thus strongly influenced by the diversity of local flora, harvesting place and season, and by the genetics of the bees [ 9 ]. Briefly, these plant resinous secretions are mixed with salivary and enzymatic secretions of honey bees, producing a cementing material, used to close open cracks occurring in beehives.…”
Section: Introductionmentioning
confidence: 99%
“…Propolis (or bee glue) is a complex mixture of molecules obtained from several resinous secretions (e.g., resins, mucilage, gums, lattices, leaf buds) collected by worker-bees from different plant species [ 8 ]. Its composition is thus strongly influenced by the diversity of local flora, harvesting place and season, and by the genetics of the bees [ 9 ]. Briefly, these plant resinous secretions are mixed with salivary and enzymatic secretions of honey bees, producing a cementing material, used to close open cracks occurring in beehives.…”
Section: Introductionmentioning
confidence: 99%
“…Propolis is defined as a balsamic and resinous product composed of a mixture of different plant parts and molecules secreted by bees [ 10 ]. Importantly, propolis is used by humans since ancient times for its medicinal properties [ 11 ].…”
mentioning
confidence: 99%
“…As a natural compound with proven pharmacological and pharmaceutical properties, propolis has actually a wide application, with antioxidant, antimicrobial, antiviral, antiparasitic, antitumor, immunomodulatory, anti-inflammatory and hepatoprotective properties [ 10 , 12 ]. Thus, these different therapeutic effects of propolis justify its potential for the development of products for use in human and animal health [ 10 ]. Concerning the use of propolis in SARS-Cov-2-infected patients, some interesting considerations must be put forward.…”
mentioning
confidence: 99%
“…Then, they add salivary enzymes to the resins and mix it with beeswax, thereby forming propolis. Thus, the chemical composition of propolis varies with the geographical region, season, surrounding flora, and bee species [13,14,27,[29][30][31][32]. Over 500 chemical compounds have been identified from various samples of propolis from different regions and seasons [27,33].…”
Section: The Chemistry Of Propolismentioning
confidence: 99%
“…Since the vegetation of different geographical regions varies, in addition to variations within the same region, and the phytochemicals in plants vary from season to season, the chemical composition of a propolis sample is determined primarily by its botanical source, the season, and the collection preferences of the bee species [13,14,29,30]. Thus, according to its botanical source, propolis may be classified into various chemotypes [30,46,47]; however, the assigned classifications unfortunately vary among authors as more types of propolis of different plant origins are being identified and characterized.…”
Section: Composition Based On Geographical Originmentioning
confidence: 99%